Comparative analysis of human leucocyte antigen between idiopathic and anti‐PD‐1 antibody induced isolated adrenocorticotropic hormone deficiency: A pilot study. (12th September 2019) - Inaba, Hidefumi; Ariyasu, Hiroyuki; Iwakura, Hiroshi; Ueda, Yoko; Kurimoto, Chiaki; Uraki, Shinsuke; Takeshima, Ken; Yamaoka, Hiroyuki; Furukawa, Yasushi; Morita, Shuhei; Nishi, Masahiro; Akamizu, Takashi
Abstract: Background: Adult‐onset idiopathic isolated adrenocorticotropic hormone deficiency (id‐IAD) is a rare disease with unknown aetiology. Recently, numerous cases of anti‐PD‐1 antibody‐induced IAD (PD1‐IAD) have been reported, but the clinical course, predictive factors and relationship to id‐IAD have not been clarified. Moreover, associations of id‐IAD and PD1‐IAD with human leucocyte antigen (HLA) require elucidation. Methods: Clinical characteristics of 13 Japanese patients with id‐IAD and eight Japanese patients with PD1‐IAD were analysed, and HLA‐typing test was performed for each patient. Allele and haplotype frequencies of the patients were compared to those of healthy Japanese controls. Results: In the HLA allele and haplotype analyses of id‐IAD, the frequencies of HLA‐C*14:02, HLA‐DPB1*05:01, HLA‐DRB1*04:05‐DQB1*04:01‐DPB1*05:01 and HLA‐DRB1*09:01‐DQB1*03:03‐DPB1*05:01 were significantly increased. On the other hand, HLA alleles account for PD1‐IAD susceptibility as follows: HLA‐DQB1*06:01, HLA‐DPB1*09:01 and HLA‐DRB5*01:02. Moreover, protective effect for HLA‐C*03:03 was suggested in combined id‐IAD and PD1‐IAD patients. Comparison of the effects of HLA on id‐IAD and PD1‐IAD revealed some differences. Alleles or haplotypes frequencies increased in id‐IAD group were as follows: HLA‐DPB1*05:01, HLA‐DRB1*09:01, HLA‐DRB4*01:03:02, HLA‐DQB1*03:03 and HLA‐DRB1*09:01‐DQB1*03:03. In clinical settings, hyponatremia, disturbance of consciousness and hypoglycaemia were less frequently seen in patients with PD1‐IAD than in patients with id‐IAD. Conclusions: Distinct clinical characteristics and predisposing HLA allele contributions were proposed between id‐IAD and PD1‐IAD. Further investigations with greater number of cases are warranted to clarify the detailed mechanisms of id‐IAD and PD1‐IAD.